High-specific-strength ceramic aluminum alloy and preparation method thereof

By adding nano-scale ceramic particles, rare earth elements and carbon nanotubes to the aluminum alloy and adopting a multi-step preparation process, the shortcomings of existing aluminum alloys and ceramic particles-enhanced aluminum alloys in terms of strength, conductivity and material uniformity are solved, and the preparation of high-specific strong ceramic aluminum alloys is achieved, with excellent mechanical properties and conductive properties.

CN119800174AInactive Publication Date: 2025-04-11ANHUI ANHUANG MACHINERY +1

Patent Information

Application Number
CN202510292776.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-13
Publication Date
2025-04-11
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing aluminum alloys and ceramic particle-reinforced aluminum alloys have shortcomings in strength, conductivity and material performance uniformity, which is difficult to meet the needs of high-performance structural materials.

Method used

High-specific strong ceramic aluminum alloys are prepared by using 5%-15% nano-scale ceramic particles and 0.1%-1% rare earth elements, combined with 0.05%-0.5% carbon nanotubes, and surface modification treatment, ultrasonic vibration assisted dispersion, stirring and casting, homogenizing heat treatment, extrusion processing and aging treatment.

Benefits of technology

It significantly improves the uniformity of the tensile strength, specific strength, conductive properties and material properties of the material, and can maintain good performance under high load environments. It is suitable for aerospace, automobiles, and electronic equipment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119800174A_ABST
    Figure CN119800174A_ABST
Patent Text Reader

Abstract

The invention discloses a high-specific-strength ceramic aluminum alloy and a preparation method thereof, and relates to the technical field of high-specific-strength ceramic aluminum alloys, and the high-specific-strength ceramic aluminum alloy comprises the following components in percentage by weight: 5-15% of nano-scale silicon carbide, aluminum nitride, aluminum oxide and other composite ceramic particles, and the balance of aluminum alloy containing magnesium, zinc and copper and impurities. 0.1%-1% of rare earth elements such as lanthanum, cerium and yttrium and 0.05%-0.5% of carbon nano tubes with the tube diameter being 5-20 nm and the length being 1-10 microns are further included, the tensile strength of the carbon nano tubes is not lower than 600 MPa, the specific strength of the carbon nano tubes is not lower than 200 MPa.cm / g, the rare earth elements refine grains and the like, the carbon nano tubes and the ceramic particles synergistically enhance the performance, and the ceramic particles are evenly dispersed and strongly combined with a matrix. The ceramic aluminum alloy is high in tensile strength and excellent in specific strength, rare earth elements refine grains to improve toughness, ceramic particles and carbon nanotubes are synergistically strengthened, the conductivity is further improved, the preparation process can overcome traditional problems, industrial production is achieved, the application prospects in the fields of aerospace, automobiles, electronics and the like are wide, and industry progress is promoted.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of high specific strength ceramic aluminum alloys, in particular to a high specific strength ceramic aluminum alloy and a preparation method thereof. Background Art

[0002] With the rapid development of modern industry, the demand for high-performance structural materials is growing. In many fields such as aerospace, automobile, machinery manufacturing, electronics, etc., materials are required to have comprehensive properties such as high strength, low density, good heat resistance, corrosion resistance and excellent electrical conductivity to meet the requirements of lightweight and high performance. Traditional metal materials, such as steel, aluminum alloy, etc., have been unable to meet the needs of modern high-end manufacturing in some aspects.

[0003] As an important lightweight metal structural material, aluminum alloy is widely used in the manufacture of various structural components due to its relatively low density, good processing performance and certain strength. However, the strength of ordinary aluminum alloy is relatively limited, which restricts its application in some key components with high strength requirements. For example, in the field of aerospace, the structural components of aircraft need to bear large loads while reducing their own weight as much as possible. Ordinary aluminum alloy may fail in high stress environments, such as deformation and fracture, and cannot meet the safety and reliability requirements of structural design.

[0004] In order to improve the performance of aluminum alloys, people have been exploring various strengthening methods, including alloying, heat treatment, and processing technology optimization. Alloying can improve the performance of aluminum alloys by adding various elements, but the excessive addition of traditional alloying elements will increase the density of the alloy, which will weaken its advantage as a lightweight material. Ceramic particle reinforced aluminum alloy is an effective way to improve the performance of aluminum alloys. Ceramic particles have high hardness, high modulus and good heat resistance. Adding them to aluminum alloys can significantly improve the strength and heat resistance of the material. However, when preparing ceramic particle reinforced aluminum alloys, many problems are usually faced. On the one hand, ceramic particles have poor wettability with aluminum alloys and are easy to agglomerate in the alloy matrix, which will lead to uneven material properties, affect the comprehensive performance of the material, and may even become a weak link in the material and reduce its reliability. On the other hand, the interface bonding strength between ceramic particles and the aluminum alloy matrix is ​​low. When subjected to external loads, cracks are easily generated at the interface, which in turn causes the destruction of the material. Moreover, when adding ceramic particles to the aluminum alloy melt in the traditional preparation process, it is difficult to ensure the uniform dispersion of ceramic particles, resulting in the inability to fully exert its strengthening effect.

[0005] At the same time, with the development of nanotechnology, nano-scale ceramic particles have received extensive attention. Their unique size effect and surface effect have brought new opportunities for strengthening aluminum alloys, but the agglomeration problem of nano-ceramic particles is more serious, and their dispersion and interface bonding in the aluminum alloy matrix are more difficult to control. In addition, in terms of comprehensive consideration of material properties, existing materials still have a large room for improvement in specific strength. Specific strength is an important indicator to measure the material's ability to withstand loads while maintaining lightweight properties, which is crucial for the application of high-performance structural materials.

[0006] While meeting the high strength requirement, some special application scenarios, such as heat dissipation components in electronic devices, also require the material to have good electrical conductivity. However, the improvement of the electrical conductivity of existing aluminum alloys and ceramic particle reinforced aluminum alloys has not received sufficient attention and optimization. In order to overcome these problems, the development of a high specific strength ceramic aluminum alloy that can not only overcome the shortcomings of traditional aluminum alloys and ceramic particle reinforced aluminum alloys, but also show excellent performance in multiple aspects such as specific strength, mechanical properties and electrical conductivity has become an important research topic in the current materials field. The key problem that the present invention aims to solve is to achieve high performance optimization by introducing innovative components and unique preparation methods. Summary of the invention

[0007] 1. Technical issues to be resolved In view of the deficiencies in the prior art, the present invention provides a high specific strength ceramic aluminum alloy and a preparation method thereof.

[0008] (II) Technical solution A high specific strength ceramic aluminum alloy, comprising, by weight percentage, 5%-15% ceramic particles, wherein the ceramic particles are a composite of one or more of nano-scale silicon carbide, aluminum nitride, and aluminum oxide, and the average particle size of the ceramic particles is 50-200nm; the remainder is aluminum alloy, wherein the main alloying elements of the aluminum alloy are one or more of magnesium, zinc, and copper, and the content of magnesium is 2%-5%, the content of zinc is 1%-3%, the content of copper is 0.5%-2%, and the rest is aluminum and unavoidable impurities, and the tensile strength of the ceramic aluminum alloy is not less than 60 0MPa, specific strength not less than 200MPa·cm³ / g; also contains 0.1%-1% rare earth elements, the rare earth elements are one or more of lanthanum, cerium, and yttrium, through the microalloying effect of rare earth elements to refine grains and improve grain boundary properties; and 0.05%-0.5% carbon nanotubes, the diameter of the carbon nanotubes is 5-20nm, the length is 1-10μm, the carbon nanotubes form a three-dimensional network structure in the alloy matrix, and cooperate with ceramic particles and aluminum alloy matrix to further enhance the mechanical properties and electrical conductivity of the material. Among them, the rare earth elements are preferentially concentrated at the grain boundaries during the solidification process of the alloy, reducing the grain boundary energy, inhibiting the migration of grain boundaries, and the effect of refining the grains reduces the average grain size by at least 10%; the three-dimensional network structure formed by the carbon nanotubes in the alloy can bear part of the load during the tensile test, increase the tensile strength of the material by at least 15%, and increase the electrical conductivity of the material by at least 20%.

[0009] Furthermore, the ceramic particles are uniformly dispersed in the aluminum alloy matrix. Through scanning electron microscopy, within a field of view of 100 μm×100 μm, the number of agglomerates of the ceramic particles does not exceed 5, and the equivalent diameter of a single agglomerate is not greater than 5 μm. Furthermore, a strong interface bond is formed between the ceramic particles and the aluminum alloy matrix through an interface reaction, and a reaction layer with a thickness of 5-50 nm is formed at the interface. The phase of the reaction layer is mainly an intermetallic compound, and its chemical bond energy is not less than 300 kJ / mol, which ensures the bonding strength between the ceramic particles and the aluminum alloy matrix, thereby effectively transferring the load.

[0010] Furthermore, the aluminum alloy matrix has an equiaxed crystal structure with a grain size of 20-50 μm, and the comprehensive performance of the material is improved through grain boundary strengthening and second phase strengthening in synergy with ceramic particles. Specifically, grain boundary strengthening is through the segregation of alloy elements at grain boundaries, which increases the resistance to dislocation movement at grain boundaries and increases the yield strength of the material by at least 20%; second phase strengthening is due to the ceramic particles as second phase particles, which produce a pinning effect on dislocation movement, and increases the tensile strength of the material by at least 30%.

[0011] Further, the following steps are included: The ceramic particles are surface modified by using one or more of silane coupling agent, titanate coupling agent or stearic acid, the amount of coupling agent is 1%-3% of the weight of the ceramic particles, stirring reaction is carried out at 50-80°C for 1-3 hours, the stirring speed is 200-400rpm, so that the coupling agent and the ceramic particles are fully contacted and reacted, and then washed with anhydrous ethanol 2-3 times, the volume of anhydrous ethanol used for each washing is 3-5 times the volume of the ceramic particles, and dried in a vacuum drying oven after washing, the drying temperature is 60-80°C, the drying time is 4-8 hours, the hydroxyl content on the surface of the dried ceramic particles is reduced by at least 80%, and its dispersibility and compatibility in aluminum alloys are improved.

[0012] Weigh the aluminum alloy raw materials according to the designed proportion, and melt them at 700-800℃ in a furnace equipped with an electromagnetic stirring device. The frequency of the electromagnetic stirring is 10-50Hz, and the stirring intensity is 50-200A to ensure that the alloy elements are fully melted and evenly distributed. During the smelting process, a refining agent is added for degassing and refining. The amount of the refining agent added is 0.5%-1% of the weight of the aluminum alloy raw material. The refining time is 10-20 minutes. The refining agent is one or more of hexachloroethane, magnesium chloride or calcium fluoride, and the particle size of the refining agent is 10-30 mesh. The diameter of the bubbles generated during the refining process does not exceed 1mm, ensuring the refining effect while reducing the introduction of impurities.

[0013] The surface-modified ceramic particles are added to the smelted aluminum alloy liquid, and ultrasonic vibration is used to assist dispersion. The ultrasonic power is 1-3kW, the frequency is 20-40kHz, and the dispersion time is 5-10 minutes. The horn of the ultrasonic vibration device is made of titanium alloy, and the matching degree between its resonant frequency and the ultrasonic power frequency is not less than 95%. The amplitude of the horn is 20-50μm, which improves the efficiency of ultrasonic energy transmission and promotes the uniform dispersion of ceramic particles. Then, stirring casting is performed at 750-850℃. The stirring paddle used in stirring casting is a spiral stirring paddle, the surface roughness of the paddle is Ra≤0.8μm, the distance between the stirring paddle and the bottom of the mold is 1 / 4-1 / 3 of the height of the mold, the stirring speed is 300-500rpm, and inert gas protection is introduced during stirring casting. The gas flow rate is 1-5L / min to prevent oxidation of the alloy liquid. The casting temperature control accuracy is within ±5℃ to obtain an ingot.

[0014] Furthermore, the refining agent is one or more of hexachloroethane, magnesium chloride or calcium fluoride, and the particle size of the refining agent is 10-30 meshes, which ensures the refining effect while reducing the introduction of impurities. The refining agent is added in batches, and the amount of each batch does not exceed 30% of the total amount of the refining agent, and each addition is separated by 2-5 minutes, so that the refining agent is evenly dispersed in the aluminum alloy liquid, and the degassing refining effect is improved.

[0015] Furthermore, during the ultrasonic vibration-assisted dispersion process, the horn of the ultrasonic vibration device is made of titanium alloy, and the matching degree between its resonant frequency and the ultrasonic power frequency is not less than 95%, which improves the efficiency of ultrasonic energy transmission and promotes the uniform dispersion of ceramic particles. The depth of the horn immersed in the aluminum alloy liquid is 1 / 3-1 / 2 of the depth of the molten pool, ensuring that the ultrasonic energy is evenly distributed in the molten pool.

[0016] Furthermore, the stirring paddle used in the stirring casting is a spiral stirring paddle, the surface roughness of the paddle is Ra≤0.8μm, and the distance between the stirring paddle and the bottom of the mold is 1 / 4-1 / 3 of the height of the mold, so as to ensure that the aluminum alloy liquid and the ceramic particles are fully mixed and avoid excessive gas from being involved. The stirring paddle rotates counterclockwise, and during the stirring casting process, the stirring direction is changed every 5-10 minutes, and the stirring is alternated to make the alloy liquid flow more evenly.

[0017] Further, the ingot is subjected to homogenization heat treatment, which is kept at 450-550°C for 4-8 hours, with a heating rate of 50-100°C / hour and a cooling rate of 30-60°C / hour. The homogenization heat treatment is carried out in an atmosphere protection furnace, with argon as the protective gas and a gas flow rate of 3-8L / min to improve the uniformity of the alloy structure. During the homogenization heat treatment process, hot isostatic pressing technology is used with an applied pressure of 100-200MPa to further eliminate microsegregation in the alloy.

[0018] Furthermore, the ingot after homogenization heat treatment is subjected to extrusion processing, with an extrusion ratio of 10-20, an extrusion temperature of 400-500°C, an extrusion speed of 1-3mm / s, a surface roughness of the extrusion die of Ra≤0.5μm, a die made of cemented carbide, and a working band length of the die of 5-15mm, so as to further refine the grains and improve the material properties. During the extrusion process, a lubricant is used, and the lubricant is a graphite-based lubricant with a coating thickness of 0.1-0.5mm, so as to reduce friction during the extrusion process and improve the surface quality of the extruded parts.

[0019] Furthermore, the extruded material is subjected to aging treatment, which is kept at 150-200°C for 2-6 hours. The temperature uniformity of the aging treatment equipment is within ±3°C, which stabilizes the alloy structure and improves the strength and hardness of the material. The aging treatment equipment uses oil bath heating, and the thermal conductivity of the oil bath medium is 0.1-0.3W / (m·K), which ensures the temperature uniformity during the aging process. After aging treatment, the hardness of the material is increased by at least 15%, and the tensile strength is increased by at least 20%.

[0020] 3. Beneficial technical effects Compared with the prior art, the present invention has the following beneficial effects: In terms of material properties, the ceramic aluminum alloy exhibits excellent mechanical properties by optimizing the composition and structure. Its tensile strength is not less than 600MPa, and its specific strength is not less than 200MPa·cm³ / g. It can withstand large loads without deformation or fracture, providing a higher safety factor for structural components. The addition of rare earth elements refines the grains, improves the grain boundary properties, enhances the grain boundary strength, and improves the toughness and fatigue resistance of the material. The composite use of nano-scale ceramic particles and carbon nanotubes forms a good synergistic strengthening effect, significantly improves the strength and hardness of the material, and the three-dimensional network structure of carbon nanotubes further improves the electrical conductivity of the material, providing possibilities for applications such as electronic equipment and electromagnetic shielding. The uniform dispersion and strong interface bonding of ceramic particles in the aluminum alloy matrix avoid the weakening of performance due to agglomeration and interface defects, and ensure the uniformity and reliability of material performance.

[0021] In terms of preparation technology, by precisely controlling various process parameters, such as surface modification, ultrasonic vibration assisted dispersion, stirring casting, homogenization heat treatment, extrusion processing and aging treatment, the problems of ceramic particle agglomeration and weak interface bonding in traditional preparation processes can be effectively overcome. The refined operation of each step, such as the batch addition of refining agent, the optimization of ultrasonic vibration device, the alternating stirring of stirring casting, the application of hot isostatic pressing technology, etc., improves the quality and performance consistency of the material. This preparation method is highly operable and can realize large-scale industrial production, providing a solid foundation for the widespread application of high-performance ceramic aluminum alloys.

[0022] At the same time, due to its high specific strength and excellent comprehensive performance, this high specific strength ceramic aluminum alloy can reduce the weight of aircraft in the aerospace field, improve fuel efficiency and flight performance; in automobile manufacturing, it can improve the safety and maneuverability of vehicles and reduce energy consumption; in electronic equipment, it can be used as a heat dissipation and conductive component to meet its requirements for strength and conductivity. In short, the present invention brings broad prospects for the development and application of high-performance structural materials, and is expected to promote technological progress in multiple industrial fields. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 The present invention is a schematic diagram of the steps of preparing a high specific strength ceramic aluminum alloy. DETAILED DESCRIPTION

[0024] refer to Figure 1 The present invention discloses a high specific strength ceramic aluminum alloy and a preparation method thereof, including the following embodiments: Example 1

[0025] This embodiment prepares a high specific strength ceramic aluminum alloy, and the specific steps are as follows: Surface modification of ceramic particles: Nano silicon carbide ceramic particles were selected and reacted with 2% by weight of silane coupling agent at 70°C and 300 rpm for 2 hours. Then, the particles were washed with anhydrous ethanol 3 times the volume of the ceramic particles for 3 times, and the supernatant was poured out after each washing. The washed ceramic particles were dried in a vacuum drying oven at 70°C for 6 hours to obtain surface-modified ceramic particles.

[0026] Aluminum alloy raw material smelting: Weigh an aluminum alloy raw material containing 3% magnesium, 2% zinc, 1% copper and the balance aluminum, place it in a furnace equipped with an electromagnetic stirring device (frequency of 30 Hz, stirring intensity of 120A), and smelt it at 750°C. Add 0.8% by weight of hexachloroethane (particle size of 20 mesh) as a refining agent, add it in batches, each batch adding 25% of the total amount of the refining agent, with an interval of 3 minutes, and refine for 15 minutes.

[0027] Compounding and Casting: The modified ceramic particles were added to the molten aluminum alloy liquid, and ultrasonic vibration was used to assist dispersion. The ultrasonic power was 2kW, the frequency was 30kHz, the immersion depth of the amplitude rod was 1 / 2 of the molten pool depth, and the dispersion was 8 minutes. After that, at 800°C, a spiral stirring paddle (the surface roughness Ra of the paddle was 0.7μm, and the distance between the stirring paddle and the bottom of the mold was 1 / 3 of the mold height) was used for stirring casting at a speed of 400rpm, and 3L / min of argon gas protection was introduced at the same time. The casting temperature was controlled with an accuracy of ±5°C to obtain an ingot.

[0028] Subsequent processing: The ingot was subjected to homogenization heat treatment at 500°C, heated at a rate of 80°C / hour, kept at this temperature for 6 hours, and then cooled at a rate of 45°C / hour. At the same time, hot isostatic pressing technology was used, a pressure of 150MPa was applied, and the process was carried out under the protection of argon gas (flow rate of 5L / min).

[0029] Then, the extrusion process was carried out with an extrusion ratio of 15, an extrusion temperature of 450°C, an extrusion speed of 2 mm / s, and a die (surface roughness Ra of 0.3 μm, working band length of 10 mm) coated with a 0.3 mm thick graphite-based lubricant.

[0030] Finally, the extruded material was aged in an oil bath at 180°C for 4 hours. The thermal conductivity of the oil bath medium was 0.2W / (m·K), and the temperature uniformity of the aging treatment equipment was ±3°C. Example 2

[0031] In this embodiment, another high specific strength ceramic aluminum alloy is prepared, and the steps are as follows: Surface modification of ceramic particles: Nano-alumina and aluminum nitride (mass ratio of 1:1) were used as ceramic particles, and 1.5% by weight of titanate coupling agent was stirred at 60°C and 250 rpm for 1.5 hours. Then, the particles were washed twice with anhydrous ethanol 4 times the volume of the ceramic particles, and dried in a vacuum oven at 75°C for 5 hours.

[0032] Aluminum alloy raw material smelting: An aluminum alloy raw material containing 4% magnesium, 1.5% zinc, 1.5% copper and the balance aluminum was weighed, smelted at 720°C, 0.6% by weight of magnesium chloride (particle size 15 mesh) was added as a refining agent, and refined for 12 minutes with an electromagnetic stirring frequency of 20 Hz and a stirring intensity of 80A.

[0033] Compounding and Casting: The modified ceramic particles were added to the aluminum alloy liquid, and ultrasonic vibration was used to assist dispersion (ultrasonic power 1.5kW, frequency 25kHz, immersion depth of the horn was 1 / 3 of the molten pool depth) for 6 minutes. At 780°C, a spiral stirring paddle (paddle roughness Ra was 0.6μm, and the stirring paddle distance from the bottom of the mold was 1 / 4 of the mold height) was used for stirring casting at 350rpm, 2L / min argon was introduced, and the casting temperature accuracy was controlled at ±5°C.

[0034] Subsequent processing: The ingot was subjected to homogenization heat treatment at 480°C, with a heating rate of 60°C / hour, holding time of 5 hours, a cooling rate of 35°C / hour, a hot isostatic pressing pressure of 120MPa, and an argon flow rate of 4L / min.

[0035] The extrusion process was performed with an extrusion ratio of 12, an extrusion temperature of 420°C, an extrusion speed of 1.5 mm / s, and a die (surface roughness Ra of 0.4 μm, working band length of 8 mm) using a graphite-based lubricant (thickness of 0.2 mm).

[0036] Finally, the product was aged in an oil bath at 160°C for 3 hours, and the thermal conductivity of the oil bath medium was 0.15 W / (m·K) to ensure temperature uniformity. Example 3

[0037] The preparation process of the high specific strength ceramic aluminum alloy of this embodiment is as follows: Surface modification of ceramic particles: Nano-silicon carbide, aluminum nitride, and aluminum oxide (mass ratio 2:1:1) were selected as ceramic particles and reacted with 2.5% by weight of stearic acid at 80°C and 350 rpm for 3 hours. The particles were washed three times with anhydrous ethanol 5 times the volume of the ceramic particles and dried in a vacuum oven at 65°C for 7 hours.

[0038] Aluminum alloy raw material smelting: An aluminum alloy raw material containing 2.5% magnesium, 2.5% zinc, 0.8% copper and the balance aluminum was weighed, smelted at 780°C, and 0.7% by weight of calcium fluoride (particle size 25 mesh) as a refining agent was added in 3 batches, with an interval of 4 minutes between each batch. The refining lasted for 18 minutes, with an electromagnetic stirring frequency of 40 Hz and a stirring intensity of 180A.

[0039] Compounding and Casting: The modified ceramic particles were added to the molten aluminum alloy liquid, and ultrasonic vibration was used to assist the dispersion (ultrasonic power 2.5kW, frequency 35kHz, immersion depth of the amplitude transformer was 1 / 2.5 of the molten pool depth) for 7 minutes. At 830°C, the spiral stirring paddle (paddle roughness Ra was 0.75μm, the stirring paddle distance from the bottom of the mold was 1 / 3.5 of the mold height) was stirred at 450rpm, 4L / min argon was introduced, and the casting temperature accuracy was ±5°C.

[0040] Subsequent processing: The ingot was subjected to homogenization heat treatment at 520°C, with a heating rate of 70°C / hour, holding time of 7 hours, a cooling rate of 50°C / hour, a hot isostatic pressing pressure of 180 MPa, and an argon flow rate of 6 L / min.

[0041] Extrusion processing, extrusion ratio 18, extrusion temperature 480 ° C, extrusion speed 2.5 mm / s, die (surface roughness Ra 0.45 μm, working belt length 12 mm) coated with 0.4 mm graphite-based lubricant.

[0042] The oil bath was aged for 5 hours at 190°C, and the thermal conductivity of the oil bath medium was 0.25W / (m·K) to ensure temperature uniformity.

[0043] Comparative Example: This comparative example adopts the traditional aluminum alloy preparation method without adding ceramic particles and innovative components. The specific steps are as follows: Aluminum alloy melting: An aluminum alloy raw material containing 3% magnesium, 2% zinc, 1% copper and the balance aluminum was weighed and smelted at 750° C. in an ordinary furnace without using a refining agent and without performing any special stirring treatment.

[0044] Casting and processing: The molten aluminum alloy liquid is directly poured into an ordinary mold and cooled and cast in an atmospheric environment without subsequent homogenization heat treatment, extrusion processing and aging treatment.

[0045] It can be seen from the above examples 1-3 that the high specific strength ceramic aluminum alloy and the preparation method thereof of the present invention can be used to prepare a material with excellent performance, which has good specific strength, tensile strength, hardness, electrical conductivity, etc., and the internal structure of the material is uniform, and the ceramic particles have good dispersion. However, the material obtained by the traditional aluminum alloy preparation method in the comparative example is obviously inferior to the high specific strength ceramic aluminum alloy of the present invention in terms of strength, hardness, electrical conductivity, etc., and the material has poor uniformity of organization and is difficult to meet the requirements of high-performance structural components, which fully reflects the advantages of the present invention.

[0046] By comparing different embodiments and comparative examples, the high specific strength ceramic aluminum alloy and the preparation method thereof of the present invention can be comprehensively evaluated and verified, providing a basis for further optimizing the material and its preparation process, and also providing a variety of possible technical solutions for its application in the fields of aerospace, automobile, electronics, etc.

[0047] This table compares the performance differences of Example 1, Example 2, Example 3 and the comparative example in terms of tensile strength, specific strength, grain size, ceramic particle agglomeration number and electrical conductivity. It can be seen that the various performance indicators of Examples 1-3 show better performance than the comparative example due to the use of the high specific strength ceramic aluminum alloy and its preparation method of the present invention, which fully reflects the advantages of the present invention in improving material performance. Among them, tensile strength and specific strength reflect the ability of the material to bear loads, grain size shows the microstructural characteristics of the material, ceramic particle agglomeration number reflects the uniformity of the material organization, and electrical conductivity represents the conductive performance of the material, which comprehensively demonstrates the value of the present invention from multiple key indicators.

[0048] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A high specific strength ceramic aluminum alloy, characterized in that: By weight percentage, it contains 5%-15% ceramic particles, which are a composite of one or more of nano-scale silicon carbide, aluminum nitride, and aluminum oxide, with an average particle size of 50-200nm, and the balance is aluminum alloy, the main alloying elements of the aluminum alloy are one or more of magnesium, zinc, and copper, and the magnesium content is 2%-5%, the zinc content is 1%-3%, and the copper content is 0.5%-2%. It also contains 0.1%-1% of rare earth elements and 0.05%-0.5% of carbon nanotubes; the rare earth elements are one or more of lanthanum, cerium, and yttrium, and the microalloying effect of the rare earth elements is used to refine the grains and improve the grain boundary properties; the carbon nanotubes form a three-dimensional network structure in the alloy matrix, and act synergistically with the ceramic particles and the aluminum alloy matrix.

2. The high specific strength ceramic aluminum alloy according to claim 1, characterized in that: The ceramic particles are uniformly dispersed in the aluminum alloy matrix. Within a field of view of 100 μm×100 μm, the number of ceramic particle agglomerates does not exceed 5, and the equivalent diameter of a single agglomerate is not greater than 5 μm. A strong interface bond is formed between the ceramic particles and the aluminum alloy matrix through an interface reaction, and a reaction layer with a thickness of 5-50 nm is formed at the interface, and the physical phase of the reaction layer is mainly an intermetallic compound.

3. The high specific strength ceramic aluminum alloy according to claim 1, characterized in that: The aluminum alloy matrix has an equiaxed crystal structure and cooperates with the ceramic particles through grain boundary strengthening and second phase strengthening. Grain boundary strengthening is achieved by the segregation of alloy elements at the grain boundaries, which increases the resistance to dislocation movement at the grain boundaries and increases the yield strength of the material by at least 20%; second phase strengthening is due to the ceramic particles acting as second phase particles, which have a pinning effect on dislocation movement and increase the tensile strength of the material by at least 30%.

4. A method for preparing a high specific strength ceramic aluminum alloy according to any one of claims 1 to 3, characterized in that: The following steps are involved: S1: Surface modification of ceramic particles is performed by using one or more of silane coupling agent, titanate coupling agent or stearic acid, the amount of coupling agent used is 1%-3% of the weight of the ceramic particles, the coupling agent and the ceramic particles are fully contacted and reacted, and then washed with anhydrous ethanol 2-3 times, and dried in a vacuum drying oven after washing, and the hydroxyl content on the surface of the ceramic particles after drying is reduced by at least 80%; S2: Weighing aluminum alloy raw materials according to the designed proportion, smelting at 700-800°C, smelting in a furnace equipped with an electromagnetic stirring device, adding a refining agent for degassing and refining during the smelting process, the refining agent is one or more of hexachloroethane, magnesium chloride or calcium fluoride, and the particle size of the refining agent is 10-30 mesh, and the diameter of bubbles generated during the refining process does not exceed 1mm; S3: Add the surface-modified ceramic particles into the smelted aluminum alloy liquid, use ultrasonic vibration to assist dispersion, and then stir-cast at 750-850°C. The stirring propeller used in the stirring casting is a spiral stirring propeller. Inert gas protection is introduced during the stirring casting process, and the gas flow rate is 1-5L / min to prevent oxidation of the alloy liquid.

5. The preparation method according to claim 4, characterized in that: The refining agent is one or more of hexachloroethane, magnesium chloride or calcium fluoride, and the particle size of the refining agent is 10-30 meshes. The refining agent is added in batches, and the amount of each batch added does not exceed 30% of the total amount of the refining agent. The interval between each addition is 2-5 minutes, so that the refining agent is evenly dispersed in the aluminum alloy liquid.

6. The preparation method according to claim 4, characterized in that: During the ultrasonic vibration-assisted dispersion process, the horn of the ultrasonic vibration device is made of titanium alloy, and the matching degree between its resonant frequency and the ultrasonic power supply frequency is not less than 95%. The depth of the horn immersed in the aluminum alloy liquid is 1 / 3-1 / 2 of the depth of the molten pool, so that the ultrasonic energy is evenly distributed in the molten pool.

7. The preparation method according to claim 4, characterized in that: The stirring paddle used in the stirring casting is a spiral stirring paddle, the surface roughness of the paddle blade Ra≤0.8μm, the distance between the stirring paddle and the bottom of the mold is 1 / 4-1 / 3 of the height of the mold, so that the aluminum alloy liquid and the ceramic particles are fully mixed and excessive gas is avoided. The rotation direction of the stirring paddle is counterclockwise. During the stirring casting process, the stirring direction is changed every 5-10 minutes.

8. The preparation method according to claim 4, characterized in that: The ingot is subjected to homogenization heat treatment at 450-550°C for 4-8 hours, with a heating rate of 50-100°C / hour and a cooling rate of 30-60°C / hour. The homogenization heat treatment is carried out in an atmosphere protection furnace, with argon as the protective gas and a gas flow rate of 3-8L / min. During the homogenization heat treatment, hot isostatic pressing technology is used with an applied pressure of 100-200MPa.

9. The preparation method according to claim 4, characterized in that: The ingot after homogenization heat treatment is extruded, with an extrusion ratio of 10-20, an extrusion temperature of 400-500°C, an extrusion speed of 1-3mm / s, a surface roughness of the extrusion die Ra≤0.5μm, the die is made of cemented carbide, and the working belt length of the die is 5-15mm. During the extrusion process, a lubricant is used, and the lubricant is a graphite-based lubricant with a coating thickness of 0.1-0.5mm.

10. The preparation method according to claim 4, characterized in that: The extruded material is subjected to aging treatment at 150-200°C for 2-6 hours. The temperature uniformity of the aging treatment equipment is within ±3°C. The aging treatment equipment adopts oil bath heating, and the thermal conductivity of the oil bath medium is 0.1-0.3W / (m·K).

Citation Information

Patent Citations

  • Preparation method of strengthened nano dispersion alloy

    CN110373565A

  • Aluminum alloy nanoparticle reinforced composite material and preparation method thereof

    CN114107778A

  • Nano-carbon reinforced aluminium composite materials and method for manufacturing the same

    KR101755988B1

  • Method for Manufacturing High Strength Ultra-Fine / Nano-Structured Al / Aln or Al Alloy / Aln Composite Materials

    US20090193935A1

Cited By

  • High-temperature-resistant composite aluminum alloy for wave soldering jig and preparation method of high-temperature-resistant composite aluminum alloy

    CN120551638A